1994
DOI: 10.1128/iai.62.9.3688-3695.1994
|View full text |Cite
|
Sign up to set email alerts
|

A neuraminidase from Streptococcus pneumoniae has the features of a surface protein

Abstract: A gene from Streptococcus pneumoniae (nanA), with features entirely consistent with a neuraminidase gene, has been sequenced. High levels of neuraminidase activity were obtained after cloning of this gene, without flanking sequences, into a high-expression vector. RNA hybridization studies have shown that the gene is transcribed by a virulent pneumococcus strain. The predicted molecular weight of the protein and certain amino acid sequences are typical of other neuraminidases. NanA contains the four copies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(46 citation statements)
references
References 43 publications
1
45
0
Order By: Relevance
“…Neuraminidase cleaves N-acetylneuraminic acid from glycolipids, lipoproteins and oligosaccharides on cell surfaces and in body fluids [39]. This may cause direct damage to the host or it may unmask potential binding sites for the organism.…”
Section: Lpxtg-anchored Surface Proteinsmentioning
confidence: 99%
“…Neuraminidase cleaves N-acetylneuraminic acid from glycolipids, lipoproteins and oligosaccharides on cell surfaces and in body fluids [39]. This may cause direct damage to the host or it may unmask potential binding sites for the organism.…”
Section: Lpxtg-anchored Surface Proteinsmentioning
confidence: 99%
“…The majority of pneumococcal glycosidases have distinct cleavage specificities (Table 1), the exception being the expression of up to three neuraminidases that cleave terminal sialic acid (NanA, NanB, and NanC) (Camara et al, 1994;Berry et al, 1996;Tettelin et al, 2001). It has been demonstrated that NanA and NanB possess neuraminidase activity; however, the enzymatic activity of NanC remains to be confirmed.…”
Section: Pneumococcal Glycosidasesmentioning
confidence: 99%
“…These enzymes are responsible for the conversion of L-alanine into D-alanine which is used in the construction of the peptidoglycan # 1996 Blackwell Science Ltd, Molecular Microbiology, 19, 1035-1045 shown as open boxes. Genes identified in the region, including the previously described nanA gene (Cámara et al, 1994), and the BOX element (Martin et al, 1992a), are indicated by shaded arrows, except for the putative 5' (unsequenced) extremity of the alaR homologue. The tentative location of the mmsA1 mutation is indicated by a vertical arrow.…”
Section: Nucleotide Sequence Of the Mmsa Regionmentioning
confidence: 99%